Mycosynthesis, characterization and antibacterial properties of AgNPs against multidrug resistant (MDR) bacterial pathogens of female infertility cases - Ponnusamy Manogaran Gopinath; Ganesan Narchonai; Dharumadurai Dhanasekaran; Anandan Ranjani; Nooruddin Thajuddin (Elsevier, 2015)
Recently, biosynthesis of silver nanoparticles using bacteria, fungus and plants has emerged as a simple and viable alternative to more complex physical and chemical synthetic procedures. The present investigation explains rapid and extracellular synthesis of silver nanoparticles using fungus Fusarium oxysporum NGD and characterization of the synthesized silver nanoparticles using UV-Vis spectroscopy, scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction analysis. The size range of the synthesized silver nanoparticles was around 16.3-70 nm. The FTIR studies showed major peaks of proteins involved in the synthesis of silver nanoparticles. Further, antibacterial effect of the silver nanoparticles against multidrug resistant pathogens Enterobacter sp. ANT 02 [HM803168], Pseudomonas aeruginosa ANT 04 [HM803170], Klebsiella pneumoniae ANT 03 [HM803169] and Escherichia coli ANT 01 [HM803167] was tested using turbidometric assay at 10, 20, 30, 40 μg AgNPs/ml alone and in combination with ampicillin using agar well diffusion assay. All the resistant bacteria were found to be susceptible to the antibiotic in the presence of the silver nanoparticles.